L'Timer : Intimità = Intimacy : l'arte contemporanea dopo l'undici settembre = contemporary art after nine eleven. - Mercurio, Gianni; Paparoni, Demetrio; Rampello, Davide (Milano : Skira editore, 2007)
Angelo, Marta dell' ; Atelier van Lieshout ; Avery, Charles ; Bas, Hernan ; Bleckner, Ross ; Bock, John ; Bonvicini, Monica ; Borremans, Michaël ; Bourgeois, Louise ; Brooks, Jason ; Brown, Don ; Brown, Glenn ; De Bruyckere, Berlinde ; Butzer, André ; Cang Xin ; Canogar, Daniel ; Carrubba, Valerio ; Cecchini, Loris ; Chapman, Dinos & Jake ; Cotton, Will ; Crewdson, Gregory ; Currin, John ; Djurberg, Nathalie ; Durant, Sam ; Emin, Tracey ; Erlich, Leandro ; Fleury, Sylvie ; Flores, Demián ; Friedman, Tom ; Galindo, Regina ; Gennari, Francesco ; Gordon, Douglas ; Hatoum, Mona ; Hirschhorn, Thomas ; Hirst, Damien ; Hopkins, James ; Immendorff, Jörg ; Joo, Michael ; Just, Jesper ; Kapoor, Anish ; Kilimnik, Karen ; Kurland, Justine ; Liu Ding ; Lockhart, Sharon ; Ma Liuming ; Marisaldi, Eva ; Masbedo ; van Meene, Hellen ; Monk, Jonathan ; Muniz, Vik ; Orta, Jorge ; Orta, Lucy ; Oursler, Tony ; Perez Bravo, Marta Maria ; Pérez, Enoc ; Phillips, Richard ; Pierson, Jack ; Puppi, Daniele ; Qingsong, Wang ; Quinn, Marc ; Renggli, David ; Roig, Bernardi ; Rottenberg, Mika ; Rovner, Michal ; Saville, Jenny ; Schinwald, Markus ; Schneider, Gregor ; Sikander, Shahzia ; Slominski, Andreas ; Smith, Kiki ; Tandberg, Vibeke ; Toderi, Grazia ; Trecartin, Ryan ; Tschäpe, Janaina ; Turk, Gavin ; Wallinger, Mark ; Wurm, Erwin ; Wüthrich, Peter ; Zhang Huan
Timer : Intimità = Intimacy : contemporary art after nine eleven. Fondazione La Biennale di Milano, 2007-03-30. 2007-06-10
boek